Galen on Apodictics - Gungov, Alexander (Studies in Medical Philosophy, 2020)
Intro -- Foreword -- Introduction -- Chapter 1 Philosophical basis of Galen's medical doctrines -- 1.1 Galen's perspective on the Hippocratic tradition -- 1.2 The significance of the doctrines of Plato and Aristotle in shaping Galen's views -- 1.3 The doctrine of Homoiomereia as the foundation of Galen's views on the microstructure of tissue -- Chapter 2 Understanding Galen's clinical experience and apodeixis -- 2.1 The semiotics of diseases. Theory of pathogenesis as a reflection of the principle of causality -- 2.2 A comprehensive understanding of philosophical theory and medical practice -- 2.3 The unity of mind and body in Galen's medicine and philisophy -- Chapter 3 Anatomical dissections as evidence in a philosophical polemic -- 3.1 Galen's method of investigation -- 3.2 The Empiricist school as the opponent of the Hippocratic tradition -- 3.3 The structure of proof in Galen -- 3.4 Galen's understanding of the natural functions of the body as a realisation of the teleological principle -- 3.5 Galen's clinical practice and physiological experiments -- Conclusion -- Bibliography.